2015
DOI: 10.1111/dar.12237
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesaemia and its potential impact on thiamine utilisation in patients with alcohol misuse at the Alice Springs Hospital

Abstract: Despite increased exposure to risk factors for Wernicke Korsakoff Syndrome, no patient had TPP concentrations below the reference range. High patient readmission and aggressive thiamine treatment policies may explain this finding. However, low magnesium may be prevalent and could contribute to impaired thiamine utilisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Thiamine is commonly found in meat (particularly pork), eggs, fish and whole grains (23). Indeed, legislation in the United States and Australia requires that certain staple foods, such as bread, be fortified with thiamine (24). Many 'breakfast cereal' type foods are also supplemented (25,26), and 'over the counter' thiamine containing multivitamins are now widely available (27).…”
Section: Thiamine Metabolismmentioning
confidence: 99%
“…Thiamine is commonly found in meat (particularly pork), eggs, fish and whole grains (23). Indeed, legislation in the United States and Australia requires that certain staple foods, such as bread, be fortified with thiamine (24). Many 'breakfast cereal' type foods are also supplemented (25,26), and 'over the counter' thiamine containing multivitamins are now widely available (27).…”
Section: Thiamine Metabolismmentioning
confidence: 99%
“…As a result, nutrient deficiencies are prevalent in this population (Chopra and Tiwari, 2012;Stroehle et al, 2012). Research has shown that subjects with AUD are deficient in or have inadequate intake of most nutrients, including: thiamine (Dastur et al, 1975;de la Monte and Kril, 2014;Boyd et al, 1981;Stroehle et al, 6 2012), riboflavin, niacin (Chopra and Tiwari, 2012;Dastur et al, 1975), B 5 (Nabipour et al, 2014), pyridoxine (Dastur et al, 1975;de la Monte and Kril, 2014;Stroehle et al, 2012), folic acid (de la Monte and Kril, 2014;Stroehle et al, 2012;Wu et al, 1975), vitamin A (Clugston et al, 2015;Ross et al, 2012), vitamin C (Boyd et al, 1981), vitamin D (Boyd et al, 1981;Quintero-Platt et al, 2015;Santolaria et al, 2000a;Wijnia et al, 2013;Wilkens Knudsen et al, 2014) vitamin E (Chopra and Tiwari, 2012;Tanner et al, 1986), vitamin K (Iber et al, 1986), magnesium (Dingwall et al, 2015;McLean and Manchip, 1999;Wilkens Knudsen et al, 2014) selenium (Tanner et al, 1986) and zinc, (de la Monte and Kril, 2014;Stroehle et al, 2012;Wilkens Knudsen et al, 2014) (Table 1). Vitamin B 12 may also be deficient; however, circulating levels may not accurately reflect the stores available for use (Kanazawa and Herbert, 1985).…”
Section: Nutritional Intake and Absorptionmentioning
confidence: 99%
“…Furthermore, there is a paucity of accurate evidence to guide clinicians regarding the dose and duration of thiamine treatment or prophylaxis for Wernicke’s encephalopathy (WE) [22, 23]. It has been observed that WE can occur in the context of apparently normal blood thiamine levels [24]. Case reports have accrued over the past four decades, which point to a role for magnesium in patients who remain refractory to thiamine treatment, and respond to concurrent administration of intravenous magnesium [2527].…”
Section: Introductionmentioning
confidence: 99%